การทำงานเป็นทีมของครูโรงเรียนวัดหลักสี่พิพัฒน์ราษฎร์อุปถัมภ์ - ใจช่วงโชติ ณัฐวดี; ชูประวัติ เพ็ญวรา (An Online Journal of Education, 2018)
This study was documentary research. The purposes of this research were 1) to study the conceptual framework of teamwork component. 2) to study the conceptual framework of team development. A documentary research was used. The research instrument was records. Data were analyzed by content analysis. The finding were as follow: 1. The conceptual framework of teamwork component composed of 1) goal setting comprised of four components as participation in goal setting, clarity of goal, understanding of the goals and, focus on goals, 2) participation comprised of six components as participation in planning, action, evaluation, decision making, problem solving and responsibility for the results of the operation, 3) Role recognition comprised of three components as structure function, perception of the work scope and perform one’s duty, 4) communication comprised of two components as commenting openly and two-way communication, 5) organizational climate comprised of three components as members’relationship, acceptance and trust and listening, 6) leadership comprised of five components as leaders and followers role play, adaptation, personal development, motivation and conflict management. 2. The conceptual framework of team development composed of 1) forming stage 2) storming stage 3) norming stage 4) performing stage and 5) adjourning stage